Development of a patient-reported outcomes symptom measure for patients with nontransfusion-dependent thalassemia (NTDT-PRO © ) - Ali Taher (2020)
© 2018 The Authors. American Journal of Hematology published by Wiley Periodicals, Inc. β-Thalassemia, a hereditary blood disorder caused by reduced or absent synthesis of the β-globin chain of hemoglobin, is characterized by ineffective erythropoiesis, and can manifest as nontransfusion-dependent thalassemia (NTDT) or transfusion-dependent thalassemia (TDT). Many patients with NTDT develop a wide range of serious complications that affect survival and quality of life (QoL). Patient-reported outcomes (PRO), including health-related QoL (HRQoL), are important tools for determining patient health impairment and selecting appropriate treatment. However, there are currently no disease-specific PRO tools available to assess symptoms related to chronic anemia experienced by patients with NTDT. This study aimed to develop a new, US Food and Drug Administration (FDA)-compliant PRO of chronic anemia symptoms, the NTDT-PRO © tool, for use in patients with NTDT. Participants had a median age of 36 years (range, 18-47) and 60% were female. The initial development of the NTDT-PRO tool involved concept-elicitation interviews with 25 patients from 3 centers (in Lebanon, Greece, and Canada); subsequent interview discussions and clinical input resulted in the generation of 9 items for inclusion in the draft NTDT-PRO. Following a round of cognitive interviews involving 21 patients from 2 centers (in Lebanon and Greece), 4 items (Pain, Headaches, Ability to Concentrate, and Paleness) were removed from the draft NTDT-PRO. The final NTDT-PRO comprises 6 items that measure Tiredness, Weakness, and Shortness of Breath, with or without Physical Activity. The NTDT-PRO is a new disease-specific HRQoL tool for patients with NTDT, developed using a thorough methodology based on FDA 2009 PRO development guidelines.